2015
DOI: 10.1177/1040638715576564
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel hydrolysis probe real-time polymerase chain reaction for agamid adenovirus 1 in the central bearded dragon (Pogona vitticeps)

Abstract: Adenoviruses are nonenveloped DNA viruses that range from 60 to 100 nm in diameter. Infections with adenoviruses are well documented, and have been reported in all of the bony vertebrates, including squamates, from which the genus Atadenovirus likely originated. 3,5,19 Currently, there are 5 accepted genera of adenoviruses within the family Adenoviridae: Atadenovirus (predominantly in squamate hosts), Aviadenovirus (in avian hosts), Ichtadenovirus (isolated from a white sturgeon), Mastadenovirus (in mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…We decided to screen each dragon using two different PCRs that were capable to detecting adenoviruses in bearded dragons. The PCR described by Fredholm et al (2015) was designed to specifically detect agamid adenovirus-1, which is the most commonly reported adenovirus infection of bearded dragons (Kübber-Heiss et al, 2006;Abbas et al, 2012;Kubiak, 2013;Doneley et al, 2014;Fredholm et al, 2015;Schilliger et al, 2016). In the study by Fredholm et al (2015), this PCR was shown to be able to detect this virus in more samples than the pan-adenovirus PCR described by Wellehan et al (2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…We decided to screen each dragon using two different PCRs that were capable to detecting adenoviruses in bearded dragons. The PCR described by Fredholm et al (2015) was designed to specifically detect agamid adenovirus-1, which is the most commonly reported adenovirus infection of bearded dragons (Kübber-Heiss et al, 2006;Abbas et al, 2012;Kubiak, 2013;Doneley et al, 2014;Fredholm et al, 2015;Schilliger et al, 2016). In the study by Fredholm et al (2015), this PCR was shown to be able to detect this virus in more samples than the pan-adenovirus PCR described by Wellehan et al (2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The PCR described by Fredholm et al (2015) was designed to specifically detect agamid adenovirus-1, which is the most commonly reported adenovirus infection of bearded dragons (Kübber-Heiss et al, 2006;Abbas et al, 2012;Kubiak, 2013;Doneley et al, 2014;Fredholm et al, 2015;Schilliger et al, 2016). In the study by Fredholm et al (2015), this PCR was shown to be able to detect this virus in more samples than the pan-adenovirus PCR described by Wellehan et al (2004). This result is consistent with our results, where of the nine animals we identified to be infected with agamid adenovirus-1, three were PCR-positive using the PCR by Fredholm et al (2015) but were PCR-negative using the PCR by Wellehan et al (2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations